2006
DOI: 10.1590/s1517-86922006000200007
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre estado nutricional e atividade física em escolares da Rede Municipal de Ensino em Corumbá - MS

Abstract: A sedentary life style is a factor of risk for the development of overweight and childhood obesity, conditions associated with dyslipidemia, arterial hypertension and insulin resistance, among other disorders. The objective of this study was to evaluate the nutritional status and the association with the profile of physical activity in Municipal Schools in Corumbá -MS. A cross-sectional study was carried out in a sample of 403 pupils, aged 7-10 years, in which children with Body Mass Index (BMI) values > 85 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
37

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 32 publications
1
6
1
37
Order By: Relevance
“…When the results of this study were compared with those of other national and international studies, higher (1,16) and lower (17)(18) percentages are also found. This divergence is not of interest since being overweight might be currently affecting a larger number of individuals earlier in life or is simply related to sampling variations and diagnosis methods.…”
Section: Discussionsupporting
confidence: 54%
“…When the results of this study were compared with those of other national and international studies, higher (1,16) and lower (17)(18) percentages are also found. This divergence is not of interest since being overweight might be currently affecting a larger number of individuals earlier in life or is simply related to sampling variations and diagnosis methods.…”
Section: Discussionsupporting
confidence: 54%
“…Estes envolveram a faixa etária de dois anos (ABRANTES; LAMOUNIER; COLOSIMO, 2003) a vinte anos de idade (GRIZ et al, 2010;PETRIBU et al, 2011) Griz et al (2010) 6,7% * * 3,7% * * 10,4% * * Leal et al (2012) 9,5% * * 3,8% * * 13,3% * * Mendonça et al (2010) 9,3% * * 4,5% * * 13,8% * * Nunes, Figueiroa e Alves (2007) 18,3% * * 6,8% * * 25,1% * * Oliveira, Cerqueira e Oliveira (2003) 9,3% * * 4,4% * * 13,7% * * Petribú et al (2011) 19% 16,4% 20,6% 5,5% 6,2% 5,1% 24,5% 22,6% 25,7% Silva (2011) 12,9% 13,0% 12,8% 12,9% 14,4% 11,4% 25,8% 27,4% 24,2% Silva, Balaban e Motta (2005) 14,5% * * 8,3% * * 22,8% * * Tassitano et al (2009) 11,5% 11,5% 11,5% 2,4% 1,9% 2,8% 13,9% 13,4% 14,3% Baruki et al (2006) 6,2% Corso et al (2012) 15,4% 15,4% 15,4% 6,1% 6,1% 6,1% 21,5% 21,5% 21,5% Cureau et al (2012) 19,6% * * 4,2% * * 23,8% 32,5% 15,1%…”
Section: Artigosunclassified
“…Para a garantia de uma vida saudável, a recomendação é realizar 60 minutos diários de atividade física moderada e intensa, de maneira acumulativa, em horas de educação física, recreação, esportes fora da escola, antes e depois dos programas da escola (BARUK et al, 2006). Pediatrics (2001), o tempo gasto por crianças e adolescentes diante da TV e com jogos eletrônicos não deve ultrapassar duas horas por dia.…”
Section: Discussionunclassified
“…Estudos pontuais desenvolvidos em escolas de ensino público e privado no Brasil revelaram que a obesidade está associada significativamente com escolaridade elevada dos pais, alta renda familiar e presença nas residências de TV, computador, telefone e video game, além de mostrarem que crianças eutróficas são mais ativas, praticam atividades físicas mais intensas e gastam menos tempo assistindo à televisão e jogando video games do que aquelas com excesso de peso (OLIVEIRA et al, 2003;BARUK et al, 2006).…”
Section: Para a American Academy Ofunclassified